The politics of multiculturalism : pluralism and citizenship in Malaysia, Singapore, and Indonesia - Hefner, Robert W., 1952- (University of Hawai'i Press, 2001)
Few challenges to the modern dream of democratic citizenship appear greater than the presence of severe ethnic, religious, and linguistic divisions in society. With their diverse religions and ethnic communities, the Southeast Asian countries of Malaysia, Singapore, and Indonesia have grappled with this problem since achieving independence after World War II. Each country has on occasion been torn by violence over the proper terms for accommodating pluralism. Until the Asian economic crisis of 1997, however, these nations also enjoyed one of the most sustained economic expansions the non-Western world has ever seen. This timely volume brings together fifteen leading specialists of the region to consider the impact of two generations of nation-building and market-making on pluralism and citizenship in these deeply divided Asian societies. Examining the new face of pluralism from the perspective of markets, politics, gender, and religion, the studies show that each country has developed a strikingly different response to the challenges of citizenship and diversity. The contributors, most of whom come Southeast Asia, pay particular attention to the tension between state and societal approaches to citizenship. They suggest that the achievement of an effectively participatory public sphere in these countries will depend not only on the presence of an independent "civil society," but on a synergy of state and society that nurtures a public culture capable of mediating ethnic, religious, and gender divides. The Politics of Multiculturalism will be of special interest to students of Southeast Asian history and society, anthropologists grappling with questions of citizenship and culture, political scientists studying democracy across cultures, and all readers concerned with the prospects for civility and tolerance in a multicultural world